Comparing the ability of cognitive and affective Theory of Mind in adolescent onset schizophrenia - Li D (Dove Medical Press, 2017)
Dandan Li,1,2,* Xiaosi Li,3,* Fengqiong Yu,1,2 Xingui Chen,2,4 Long Zhang,2,4 Dan Li,2,4 Qiang Wei,2,4 Qing Zhang,1,2 Chunyan Zhu,1,2 Kai Wang1,2,4 1Department of Medical Psychology, Anhui Medical University, Hefei, 2Collaborative Innovation Centre of Neuropsychiatric Disorders and Mental Health, Anhui Province, 3Mental Health Center of Anhui Province, 4Department of Neurology, The First Affiliated Hospital of Anhui Medical University, Hefei, China *These authors contributed equally to this work Background: Evidence in the literature suggests that there is an impairment of social cognition in schizophrenia. Theory of Mind (ToM) is defined as one’s ability to understand others’ wishes, beliefs, intentions, and other psychological states and thereby to judge others’ behavior, as an essential component of social cognition. However, there have been limited studies on social cognition, especially ToM in adolescent onset schizophrenia (AOS). The current study aims to investigate ToM abilities in adolescent schizophrenia according to various ToM subcomponents (cognitive ToM and affective ToM) and various ToM orders (first order and second order).Methods: This study examines ToM in 35 adolescent schizophrenic patients and 35 healthy adolescents using the “Yoni task” and “Faux Pas Recognition test” to assess their affective and cognitive ToM abilities.Results: In the Yoni task, patients with AOS showed differences in ToM abilities either on a different order or under different conditions. The Faux Pas Recognition task results revealed that AOS patients were not always able to recognize a faux pas or understand complicated emotions under the faux pas scenario. Furthermore, as indicated by the correlation analysis, neither cognitive ToM nor affective ToM was related to the patients’ symptoms, disease duration, dose of medication, or intelligence quotient (IQ).Conclusion: Our findings showed AOS impairment in the performance of ToM tasks. It seemed that impairment in second-order-ToM is more serious. Moreover, these deficits are largely independent of symptom clusters, disease duration, dose of medication, and IQ. It can be speculated that ToM dysfunction may be a hallmark of adolescent schizophrenia. Keywords: cognitive/affective Theory of mind, Yoni task, Faux Pas Recognition task